1996
DOI: 10.1577/1548-8675(1996)016<0840:eowsoy>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Walleye Stocking on Year-Class Strength

Abstract: The success of stocking programs involving walleye Stizostedion vitreum has frequently been judged by the contributions of the stocked walleye to the abundance of year‐classes. But evaluation methods based only on contributions to the year‐class augmented may be biased. We developed a method of estimating walleye year‐class strength based on catch‐at‐age data from routine fish population assessments. We then examined the effect of walleye stocking on the stocked year‐class and other year‐classes by using catch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 17 publications
1
27
1
Order By: Relevance
“…Thus, it is worth asking the question: Does stocking create inland fisheries consistency to meet public desires and demands as suggested conceptually by Figure 4? More recently, Santucci and Wahl (1993) observed low contributions of stocked Walleye Sander vitreus of various sizes to year-class strength, and Li et al (1996) found that Walleye stocking in lakes with poor natural reproduction did not contribute to year-classes significantly. Despite its popularity, stocking has often failed to meet these lofty goals.…”
Section: Immediate Versus Delayed Gratification In Fisheries and Wildmentioning
confidence: 99%
“…Thus, it is worth asking the question: Does stocking create inland fisheries consistency to meet public desires and demands as suggested conceptually by Figure 4? More recently, Santucci and Wahl (1993) observed low contributions of stocked Walleye Sander vitreus of various sizes to year-class strength, and Li et al (1996) found that Walleye stocking in lakes with poor natural reproduction did not contribute to year-classes significantly. Despite its popularity, stocking has often failed to meet these lofty goals.…”
Section: Immediate Versus Delayed Gratification In Fisheries and Wildmentioning
confidence: 99%
“…However, considerable uncertainty remains regarding the efficacy of different egg and larval collection methods, and the appropriate age of fish to stock. Success of supplementation programmes is typically based on estimates of contributions of stocked fish to older age classes (Li et al. 1996) or return to post stocking assessments (Walters et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, considerable uncertainty remains regarding the efficacy of different egg and larval collection methods, and the appropriate age of fish to stock. Success of supplementation programmes is typically based on estimates of contributions of stocked fish to older age classes (Li et al 1996) or return to post stocking assessments (Walters et al 1997). However, these methods are not amenable to A. fulvescens as they are not widely subject to harvest and younger age classes are not efficiently captured in surveys using standard sampling methods (Benson et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a growth rate or size-at-age threshold could be used to determine whether management action, such as stocking or fishery closure, is needed to prevent overexploitation. Although the effects of stocking walleye are mixed, such growth thresholds could also forewarn managers before the collapse of a particular stock (Kempinger and Churchill 1972;Li et al 1996aLi et al , 1996b.…”
Section: Introductionmentioning
confidence: 99%